Dancing to the tune of fourth paradigm - Zakaria, Khasiah; Zakaria, Jama'yah (Perpustakaan, Universiti Sains Malaysia and Universiti Sains Malaysia, 2017)
The world has entered a “fourth paradigm” which is more collaborative, more computational, and more data intensive than the previous experimental, theoretical, and computational paradigms. This emerging scientific paradigm is often referred to as e-science or e-research. The current study focuses on the academic librarian’s roles in coordinating “fourth paradigm” roles that have been powered by advanced computing capabilities in libraries to assist the researchers. It highlights the fact that by leveraging on technology in all parts of scientific endeavor, cyber infrastructure, and the establishment of data management and data sharing dictates by many research funding bodies, academic libraries have offered support with regard to the shifting needs of their community. The act of embedding the fourth paradigm’s role need to be explored by Malaysian librarians. This could be a role on how best to engage in e-science through the development of library-based research data services (RDS). The paradigm offers, an important far-reaching look at the rapidly developing field of data-intensive science. Librarians should engage the “fourth paradigm” roles in ensuring the profession stays relevant. The “Fourth Paradigm” taxonomy will be developed to measure characteristics of the paradigm. The categorization would be offered as part of librarian’s competency dimensions which hopefully increases the publicizing of the profession.